Società multiculturali e percorsi di integrazione Francia, Germania, Regno Unito ed Italia a confronto - CERRINA FERONI, GINEVRA; FEDERICO, VERONICA (Strumenti per la didattica e la ricerca, 2017)
Governing the complexity of contemporary multicultural societies poses major challenges and a constant tension between substantial equality, the right to difference and social order. Tools, paths and strategies to integrate different communities and individuals within the same horizon of rights and duties are essential to give life to new types of citizenship and to a new sense of belonging. The volume aims to open a critical reflection on the subject, allowing to combine the theoretical horizon with the effectiveness of the law, by analysing four relevant experiences in the European panorama: United Kingdom, France, Germany and Italy. These are experiences that propose different models and mechanisms of integration, but which are all crossed by the need to research and experiment innovative and effective paths to cope with one of the most delicate challenges of our time.